ANÁLISE DOS REQUISITOS PARA A IMPLANTAÇÃO DA FILOSOFIA LEAN GREEN CONSTRUCTION EM EDIFICAÇÕES DE PEQUENO PORTE - Gontijo, Dayana Silva Moreira; Santana, Jhonvaldo de Carvalho; Prado, Andreia Alves do (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Lean Green Construction philosophy consists in a fusion of the concepts of lean and sustainable construction. While the Lean Construction is concerned about its ventures planning and management, aiming for the reduction of stages that don't add value to the final product, as well as the minimization of the wastes related to production process, the Green Building takes into account the project sustainability in all its stages, since the natural resources extraction until the end of its lifespan, caring not only about the building, but also about the surrounding environment. In this context, certifications that utilize criteria to assess how much "green" a building is were created. The present work has as purpose to analyze the requirements to the Lean Green Construction philosophy deployment, aiming to direct the appropriateness of these small size single-family residential constructions to this philosophy. To this end, a bibliographic review was taken place, evaluating the influence of the Lean Construction concepts in to the sustainable building constructions, besides a comparative analysis among the LEED, AQUA - HQE and Casa Azul seals, looking for criteria to the Lean Green concepts deployment to small size projects.